Interaction of Skating Agility Tests and Postural Stability in Hockey Players - Jaroslav Broďáni; Matúš Guzman; Roman Vala; Viktor Huszár (OVS LLC, 2024)
Study purpose. In this work, we point out the interaction of complex postural stability (CPS) and skating agility tests among pupils in the hockey club HK Nové Zámky. We determined postural stability using the SEBT and agility with skating tests. We expected a significant interaction between performance in skating agility tests and CPS for both standing legs, which was most closely identified with the eight-item SEBT test. Materials and methods. The level of CPS was characterized by descriptive statistics. Laterality between right and left standing leg was assessed by t-test and Cohen's "d". The relationships between CPS and skating agility tests were determined by Pearson's correlation coefficient "r". Predictors were selected by stepwise regression. Statistical significance of differences and relationships was assessed at the 5% significance level. Results. The results showed no differences in the laterality of the CPS between the right and left standing leg. Correlation analysis demonstrated the interactions of the left and right standing leg with all skating agility tests. Stepwise regression was used to select the tests that were most identified with the performance on the eight-item SEBT test in terms of their skating expression. The Illinois test has the most significant informational power for CPS. Conclusions. The presence of positive interactions between skating agility and CPS in hockey players point to the importance of a balanced and stable stance of both legs in all directions. The perfect balance and stability of hockey players eliminates the fluctuations caused by skating movement in all directions and facilitates their execution without major changes in dynamic performance. The chance of shortening the activation time of the muscle chains involved in the technique of performing the test also increases significantly, or in the very structure of technique - the economics of ice hockey players' skating.